Analysis of Oocyte and Embryo Numbers, and Pregnancy Rate in Patients Undergone In Vitro Fertilization with Long and Short Protocols - Shafira, Nadia (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objectives: To compare the oocyte count, embryo count, pregnancy rate, and the presence of OHSS in patients undergoing In Vitro Fertilization (IVF) with long and short protocols at Yasmin Clinic, Dr. Cipto Mangunkusumo Hospital, Jakarta. Methods: A cross sectional study was done at Yasmin Reproductive Clinic, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Data was collected from the medical records of 200 infertile women undergoing IVF, 100 women with long protocols and the other 100 with short protocols. Variables compared in these 2 groups are the oocyte count, embryo count, the pregnancy rate, and presence OHSS using Mann-Whitney U Test with SPSS 11 Program. Result: From 200 women undergoing IVF procedure, 45.5% of them aged between 35-40 years old, with the youngest is 22 years old and the oldest is 48 years old (average age=35 years, SD=4.7), and almost half of them (45%) have BMI between 18.01-23.00 kg/m2. 185 women has primary infertility. These subjects came to the clinic mostly due to male factor (23.5%), idiopathic cause (19%), and ovulation disturbance (13%), whilst endometriosis, tubal factor, and other factors take just little percentage. When compared between long and short protocols, the number of oocyte retrieved is significantly different (p=0.007, CI=5.84-7.11), whereas embryo numbers (p=0.054, CI=1.80-2.39) and the pregnancy rate (p=0.525, CI=0.21-0.33) found to be not significantly different. There were 2 cases of moderate OHSS developed in the long protocol group. Conclusion: Although the number of embryo produced and the pregnancy rate are found to be not significantly different between the two groups, long protocol of IVF is found to produce more oocyte to be retrieved and develop more OHSS events compared to short protocol. Due to this result, GnRH antagonist can be considered when planning an IVF procedure. However, a longitudinal multicenter study with larger sample size is needed to validate the current data. [Indones J Obstet Gynecol 2012; 36-2: 95-9] Keywords: in vitro fertilization, long protocol, pregnancy rate, short protocol